Liver Transplantation in Patients with Alcoholic Liver Disease: A Retrospective Study. (1st December 2017) - Vassallo, Gabriele A; Tarli, Claudia; Rando, Maria M; Mosoni, Carolina; Mirijello, Antonio; Agyei-Nkansah, Adwoa; Antonelli, Mariangela; Sestito, Luisa; Perotti, Germano; Di Giuda, Daniela; Agnes, Salvatore; Grieco, Antonio; et al.
Abstract : No difference was found between patients transplanted for alcoholic cirrhosis and viral cirrhosis in term of survival rate. Only patients transplanted for viral cirrhosis presented primary liver disease recurrence. A higher rate of cancer development was found in patients transplanted for alcoholic cirrohosis. This complication was associated with post-trasplant smoking. Abstract: Aim: Alcoholic liver disease (ALD) is the most common liver disease in the Western World. Liver transplantation (LT) is the treatment for end-stage ALD. However, many transplant centers are still reluctant to transplant these patients because of the risk of alcohol relapse, recurrence of the primary liver disease and associated post-transplant complications. We examined survival rate, prevalence of primary liver disease recurrence, re-transplantation and post-transplant complications among transplanted patients for alcoholic cirrhosis compared with those transplanted for viral cirrhosis. Methods: data about patients transplanted for alcoholic and viral cirrhosis at the Gemelli Hospital from January 1995 to April 2016 were retrospectively collected. Survival rate was evaluated according to the Kaplan–Meier method. Recurrence was defined as histological evidence of primary liver disease. Data on the onset of complication, causes of death and graft failure after liver transplant were analyzed. Results: There was no statistically significant difference regarding survival rate between the two groups. Only patients transplanted for viral cirrhosis presented with primary liver disease recurrence. There was a higher rate of cancer development in patients transplanted for alcoholic cirrhosis. Cancer was the major cause of death in this population. Risk factors associated with the onset of cancer were a high MELD score at the transplant time and smoking after transplantation. Conclusion: ALD is a good indication for LT. Patients transplanted for alcoholic cirrhosis should receive regular cancer screening and should be advised against smoking. Short Summary: No difference was found between patients transplanted for alcoholic cirrhosis and viral cirrhosis in term of survival rate. Only patients transplanted for viral cirrhosis presented primary liver disease recurrence. A higher rate of cancer development was found in patients transplanted for alcoholic cirrohosis. This complication was associated with post-trasplant smoking.